2006
DOI: 10.1093/jmt/43.2.136
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Music Therapy on Pediatric Patients' Pain and Anxiety During Donor Site Dressing Change

Abstract: The purpose of this study was to assess the effects of music therapy on pain and anxiety in pediatric burn patients during a donor site dressing change. Fourteen subjects were randomly selected to participate in this study. The experiment was conducted in the Reconstructive Unit of Shriners Burns Hospital-Boston. The experimental group's intervention consisted of live music and was compared to a control group whose intervention was verbal interaction. Psychological, behavioral, and physiological data were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 0 publications
0
87
0
3
Order By: Relevance
“…Although, several investigators have evaluated efficacy of western music in reducing pain, its superiority over placebo was not unequivocally demonstrated. 10,13,14,20 This is the first study that has evaluated the efficacy of Indian classical instrumental music and found that it is more efficacious than placebo in reducing pain associated with venepuncture in children. In view of the lowest pain scores being associated with EMLA application and these scores being significantly lower than those 0 1 1 1 2 7 5 3 Investigator 0 min 1 3 2 2 2 4 2 3 7 9 2 8 1 m i n 0 2 2 1 1 2 1 2 4 8 4 6 5 m i n 0 1 1 0 0 2 2 1 2 7 5 3 Independent 0 min 1 4 3 2 2 4 2 2 7 9 2 8 observer 1 min 0 2 2 1 1 3 2 1 3 8 5 5 5 m i n 0 1 1 0 0 2 2 1 2 6 4 3 Abbreviations: Md: Median; IQR-Inter-quartile distance; LA: Local anesthetic group (EMLA); VAS: Visual analog scale scores LA: Local anesthetic group; VAS: Visual analog scale score †: Comparison of pain (VAS) scores between local anesthetic and music groups, at 0min ‡: Comparison of pain (VAS) scores between local anesthetic and music groups, at 1min §: Comparison of pain (VAS) scores between local anesthetic and music groups, at 5min associated with music at least at some time-points; it could be recommended that Indian classical instrumental music could be used in reducing venepuncture-related pain in children, when LA application does not seem to be feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, several investigators have evaluated efficacy of western music in reducing pain, its superiority over placebo was not unequivocally demonstrated. 10,13,14,20 This is the first study that has evaluated the efficacy of Indian classical instrumental music and found that it is more efficacious than placebo in reducing pain associated with venepuncture in children. In view of the lowest pain scores being associated with EMLA application and these scores being significantly lower than those 0 1 1 1 2 7 5 3 Investigator 0 min 1 3 2 2 2 4 2 3 7 9 2 8 1 m i n 0 2 2 1 1 2 1 2 4 8 4 6 5 m i n 0 1 1 0 0 2 2 1 2 7 5 3 Independent 0 min 1 4 3 2 2 4 2 2 7 9 2 8 observer 1 min 0 2 2 1 1 3 2 1 3 8 5 5 5 m i n 0 1 1 0 0 2 2 1 2 6 4 3 Abbreviations: Md: Median; IQR-Inter-quartile distance; LA: Local anesthetic group (EMLA); VAS: Visual analog scale scores LA: Local anesthetic group; VAS: Visual analog scale score †: Comparison of pain (VAS) scores between local anesthetic and music groups, at 0min ‡: Comparison of pain (VAS) scores between local anesthetic and music groups, at 1min §: Comparison of pain (VAS) scores between local anesthetic and music groups, at 5min associated with music at least at some time-points; it could be recommended that Indian classical instrumental music could be used in reducing venepuncture-related pain in children, when LA application does not seem to be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that western music is capable to minimize pain. [13][14][15] Indian classical music has soothing qualities that change the mood of dejected, depressed and distressed individuals facing stressful situations. 16,17 However, its role in reducing of pain has not been evaluated.…”
mentioning
confidence: 99%
“…Cited sources of information on the Gate Control Theory of Pain included: Livingston, 1943Livingston, , 1953Melzack 1961Melzack , 1973Melzack and Wall, 1965;and Sarafino, 1997. Interestingly, the Gate Control Theory of Pain was referenced by authors who adopted differing approaches to music therapy as procedural support including musical alternate engagement (Noguchi, 2006;Whitehead-Pleaux, Baryza, & Sheridan, 2006;Whitehead-Pleaux, Zebrowski, Baryza, & Sheridan, 2007;Wolfe & Waldon, 2009), integration (Loewy et al, 1997), and various forms of music-assisted relaxation . Authors in the reviewed publications cited additional theories related to pain perception, including multidimensional models of pain perception, wherein sensory-discriminative, cognitive-evaluative, and motivationalaffective dimensions of pain perception may be altered to therapeutic benefit (Melzack, Weisz, & Sprague, 1963;Weisenberg, 1994).…”
Section: Theoretical Assumptionsmentioning
confidence: 99%
“…(Loewy, 1999, p. 199) Assessment occurring prior to a procedure or assessment taking place throughout the course of the procedure determines what form of procedural support is chosen, and how the provision of procedural support may change over time (Daveson, 1999;Frattiane et al, 2001;Loewy et al, 1997;Turry, 1997;Whitehead-Pleaux et al, 2006;Wolfe & Waldon, 2009). Assessment may determine what type of music is used, how the music is used, the level of patient engagement required, and how the procedural support approach can align with the patient's coping resources (Walworth, 2005;Whitehead-Pleaux et al, 2006;Whitehead-Pleaux, Zebrowski, Baryza, & Sheridan, 2007).…”
Section: Individualized Approachmentioning
confidence: 99%
“…The use of music for the reduction of pain has been researched in hospital and post-operation settings [122]- [124], for pediatric pain [125]- [127], and pain conditions such as labor, chronic, acute, and malignant pain [128]- [130]. However, a systematic review showed minor benefits of music therapy in pain treatment and concluded that the role of music was questionable in its clinical importance [131].…”
Section: Other Stimulation Modalitiesmentioning
confidence: 99%